Transtorno cognitivo e síndrome metabólica em idosos usuários da atenção básica do Sistema Único de Saúde em uma cidade do interior de São Paulo - Araújo, Renata Bezerra (2018)
The etiology of Cognitive Disorder (Cognitive Disorder) is complex. The discussion about the influence of Metabolic Syndrome (MS) with genetic and environmental factors, linked to lifestyle has gained notoriety. The objective of this dissertation was to investigate associations between MS and TC in elderly users of Basic Health Units in the city of São Carlos, in the state of São Paulo. It was a cross-sectional, quantitative, correlational study. 200 participants ≥ 65 years of age were evaluated. Instruments: Addenbrooke's Cognitive Examination-Revised Version (ACE-R), Functional Activities Questionnaire (QAF), Memory Complaint Scale (EQM A and B), Geriatric Depression Scale (GDS), Classification Criteria Economics Brazil (CCEB) and sociodemographic and clinical questionnaire prepared for the study.